Regulation of aspartokinase III synthesis in Escherichia coli: isolation of mutants containing lysC-lac fusions. - Richaud, F (1980)
Mutants containing fusions of the lac gene to the lysC gene were isolated. In these, the expression of beta-galactosidase was regulated by lysine (and arginine), as previously described for aspartokinase III.